Anaesthetic management of infant with occipital encephalocele associated with Arnold Chiari III malformation - A Case Report - Vandana Patilbuwa Pakhare; K. Naga Sri Sowmya; Mohammed Mohsin Ali; Reshma Sultana; Doli Suresh Chander (MRIMS Journal of Health Sciences)
Children with occipital meningoencephalocele associated with Arnold–Chiari III malformation present unique challenges to anesthesiologists. Meningoencephalocele is a congenital anomaly wherein meninges, brain, and cerebrospinal fluid (CSF) are herniated through defect in the skull. Challenges to anesthesiologists include difficult airway, latex allergy, bleeding, CSF loss, and autonomic disturbances. Here, we report a late case of a 9-month-old male child with occipital encephalocele associated with Arnold–Chiari III malformation. The child underwent surgical correction under general anesthesia without any adverse event. The anticipated difficult airway was secured with prior planning and teamwork. Multidisciplinary care and careful planning are essential to safeguard the perioperative outcomes for patients with meningoencephalocele wherein difficult airway, blood loss, autonomic dysfunction, and perioperative hypothermia are major concerns.